IJPS 2022
DOI: 10.36468/pharmaceutical-sciences.1012
|View full text |Cite
|
Sign up to set email alerts
|

Amycolatopsis sp. strain MN235945 Mediated Biosynthesis of Silver Nanoparticles: Characterization, Antimicrobial and Anticancer Activity against HeLa and MCF-7 Cell Lines

Abstract: Swamy et al.: Anticancer activity of Amycolatopsis sp. mediated Silver NanoparticlesThe current study investigated about the biogenic synthesis and evaluation of biological activities of Amycolatopsis sp. strain MN235945 fabricated silver nanoparticles and their characterization by ultraviolet-visible spectroscopy, fourier transform infrared spectroscopy, high resolution-transmission electron microscopy, energy dispersive X-ray spectroscopy, X-ray diffractometry and zeta potential analysis. The most potent iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…Many studies elucidated the probable modes of action for the antimicrobial mechanism shown by AgNPs, namely, the interaction between silver NPs and a bacterial cell cause cellular membrane damage, ribosome disassembly, enzyme inactivation, protein denaturation, the production of reactive oxygen species, or disruption of the electron transport chain, and cell death occurs in the pathogenic microbe. Similar results were reported by Swamy et al [ 49 ], where NPs from Amycolatopsis sp. strain MN235945 showed greater activity against E. coli , then other pathogens in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Many studies elucidated the probable modes of action for the antimicrobial mechanism shown by AgNPs, namely, the interaction between silver NPs and a bacterial cell cause cellular membrane damage, ribosome disassembly, enzyme inactivation, protein denaturation, the production of reactive oxygen species, or disruption of the electron transport chain, and cell death occurs in the pathogenic microbe. Similar results were reported by Swamy et al [ 49 ], where NPs from Amycolatopsis sp. strain MN235945 showed greater activity against E. coli , then other pathogens in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 91%
“…This significant effect of AgNPs against microbial pathogens is due to the small size and electrostatic force of the attraction between the less negative to positive charge of the AgNPs and the negatively charged microbial cell membrane; this attraction converts the cells chemical and physiological properties, which break the normal physiological properties including the permeability, respiration, etc., of cells [ 51 , 52 ]. The attachment of NPs to lipopolysaccharides in the cell membrane disrupts the cell wall and helps with the entry of the NPs into the cell, and the binding of cellular components, such as proteins, enzymes and DNA, to the NPs causes cell death [ 49 ]. AgNPs have also been reported for on regarding the generation of reactive oxygen and nitrogen species, where they create oxidative stress upon DNA, and several other cell constituents, and disturb the main functions of bacterial cells [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…A trace of elements in the form of peaks was detected together with silver ions by the EDX pattern (Figure 4c). These results confirmed the formation of the AgNPs as presented in the previous studies by Luhata and his co-workers [46] and Swamy and his colleagues [47]. The obtained diffraction pattern (XRD), the crystalline nature, and the calculated particle size (19.11 nm) using the Scherrer equation of AgNPs obtained and presented in Figure 4d were consistent with what Khane and his co-workers [27] and Loganathan and his co-workers [48] had reported, respectively.…”
supporting
confidence: 90%
“…As a result, energy production is inhibited, membrane permeability is increased, microbial DNA is interfered with, proteins are disrupted, and ROS are produced, ultimately leading to cell death (Sharma et al 2022 ). Also, the disruption of the cell wall caused by the connection of NPs to lipopolysaccharides in the cell membrane facilitates the admission of the NPs into the cell, and the binding of biological elements such as proteins, enzymes, and DNA to the NPs results in cell death (Swamy et al 2022 ). Therefore, the interaction between Ag ions and the fungal extract may be responsible for the AgNPs’ reported antibacterial activity as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%